DETERMINING THE STUDENTS’ ATTITUDE TOWARDS RESEARCH: AN EXPLORATORY FACTOR ANALYSIS - Gono Jr, Exequiel R. (European Journal of Education Studies, 2024)
This research endeavors to delve into the underlying attitudes of criminology students toward research. An extensive review of theories and literature concerning students' perceived attitudes toward various subjects was conducted to accomplish this objective. Furthermore, data were collected from 50 criminology students to gauge their attitudes towards research. Drawing from this data, a comprehensive set of statement items was formulated to capture the identified attitudes accurately. These items underwent meticulous validation by a panel of experts to ensure their reliability and relevance to the study's objectives. Subsequently, the validated items were administered to a larger sample comprising 245 criminology students. Employing Exploratory Factor Analysis, the study uncovered three primary attitudes toward research: Research Application for Education and Career, Personal Engagement and Development, and Personal Advancement. This systematic approach sheds light on the diverse perspectives of criminology students regarding research. It provides valuable insights for educators to tailor teaching methods effectively to meet students' needs and interests in research.  Article visualizations: